Contemporary Somali piracy : evaluating the effectiveness of counter-piracy measures - Tan, Cherlyn Shuyi. (2011)
This report discusses about the effectiveness of current anti-piracy measures in the Somalia basin, which includes the Gulf of Aden, the Arabian Gulf and the Indian Ocean. Currently, the anti-piracy measures can be split into two groups, namely, the industry efforts, and the international efforts. The industry efforts refer mainly to the Best Management Practices (BMP) and the usage of private armed guards. On the other hand, the international efforts looks at the measures that the governments and the international community has come up with, which includes the international conventions and laws and the deployment of naval forces. Through literature reviews, a hypothesis was drawn up to test if ship owners will most likely adhere to the BMP due to its effectiveness and ability to overcome the limitations imposed by the international measures.